Synergetic Enhancement of Thermoelectric Performance by Selective Charge Anderson Localization-Delocalization Transition in n-Type Bi-Doped PbTe/Ag2Te Nanocomposite - Lee, Min Ho; Yun, Jae Hyun; Kim, Gareoung; Lee, Ji Eun; Park, Su-Dong; Reith, Heiko; Schierning, Gabi; Nielsch, Kornelius; Ko, Wonhee; Li, An-Ping; Rhyee, Jong-Soo (ACS nano, 2019)
Considerable efforts have been devoted to enhancing thermoelectric performance, by employing phonon scattering from nanostructural architecture, and material design using phonon-glass and electron-crystal concepts. The nanostructural approach helps to lower thermal conductivity but has limited effect on the power factor. Here, we demonstrate selective charge Anderson localization as a route to maximize the Seebeck coefficient while simultaneously preserving high electrical conductivity and lowering the lattice thermal conductivity. We confirm the viability of interface potential modification in an n-type Bi-doped PbTe/Ag 2 Te nanocomposite and the resulting enhancement in thermoelectric figure-of-merit ZT. The introduction of random potentials via Ag 2 Te nanoparticle distribution using extrinsic phase mixing was determined using scanning tunneling spectroscopy measurements. When the Ag 2 Te undergoes a structural phase transition (T > 420 K) from monoclinic β-Ag 2 Te to cubic α-Ag 2 Te, the band gap in the α-Ag 2 Te increases due to the p-d hybridization. This results in a decrease in the potential barrier height, which gives rise to partial delocalization of the electrons, while wave packets of the holes are still in a localized state. Using this strategic approach, we achieved an exceptionally high thermoelectric figure-of-merit in n-type PbTe materials, a ZT greater than 2.0, suitable for waste heat power generation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Anderson localization; bulk composite; figure-of-merit; thermal conductivity; thermoelectric